Family Education in the Qur'an: A Thematic Exegesis and Modern Educational Perspectives - Jarrohhatul Masruroh (Arbain Publishing, 2026)
Family education plays a crucial role in shaping children's personality and character. Contemporary parents face various challenges in raising and educating their children in the modern era, including those within Muslim families. Family education grounded in Qur’anic values should not be understood merely through a textual approach; rather, it requires in-depth examination to uncover its relevance to contemporary life. Studies that relate Qur’anic values to modern educational theories remain relatively limited. This study aims to analyze the concept of family education based on Qur’anic verses and to identify its relevance to modern educational theory. This research employs a library research design using a descriptive-analytical qualitative approach. The primary sources consist of the Qur’an, classical and contemporary exegetical works, and literature on modern education. The findings indicate that family education from the Qur’anic perspective is consistent with educational theories proposed by modern scholars such as Talcott Parsons, Maria Montessori, and Diana Baumrind. This study is expected to contribute to the development of Islamic educational studies and serve as a reference for family education practices in the modern era.